EL HORIZONTE MEDIO EN LOS ANDES CENTRALES A TRAVÉS DE LOS TEXTILES DEL MUSEO DE AMÉRICA DE MADRID - Jiménez, María Jesús (2004)
The Collection of Pre-Hispanic Textiles in the Museum of America in Madrid, consists of almost 400 pieces from different periods and areas of the Central and SouthCentral Andes. In this article, we analyse those one which can be assigned to the Middle Horizon Period, representing different geographical areas from the South Coast to the North Coast, with some examples of “Huari” style from the Highlands. In the following pages, we will intent to describe the complex panorama of textile production during these centuries through the textiles of each region which have been found in the Collection of the Museum of America.